Buffer layers inhomogeneity and coupling with epitaxial graphene unravelled by Raman scattering and graphene peeling. (15th August 2020) - Wang, Tianlin; Huntzinger, Jean-Roch; Bayle, Maxime; Roblin, Christophe; Decams, Jean-Manuel; Zahab, Ahmed-Azmi; Contreras, Sylvie; Paillet, Matthieu; Landois, Périne
Abstract: The so-called buffer layer (BL) is a carbon rich reconstructed layer formed during SiC (0001) sublimation. The covalent bonds between some carbon atoms in this layer and underlying silicon atoms makes it different from epitaxial graphene. We report a systematical and statistical investigation of the BL signature and its coupling with epitaxial graphene by Raman spectroscopy. Three different BLs are studied: bare buffer layer obtained by direct growth (BL0 ), interfacial buffer layer between graphene and SiC (c-BL1 ) and the interfacial buffer layer without graphene above (u-BL1 ). To obtain the latter, we develop a mechanical exfoliation of graphene by removing an epoxy-based resin or nickel layer. The BLs are ordered-like on the whole BL growth temperature range. BL0 Raman signature may vary from sample to sample but forms patches on the same terrace. u-BL1 share similar properties with BL0, albeit with more variability. These BLs have a strikingly larger overall intensity than BL with graphene on top. The signal high frequency side onset upshifts upon graphene coverage, unexplainable by a simple strain effect. Two fine peaks (1235, 1360 cm −1 ), present for epitaxial monolayer and absent for BL and transferred graphene. These findings point to a coupling between graphene and BL. Graphical abstract: Image 1